THE RELATIONSHIP BETWEEN ENZYMES IN BLOOD PLASMA AND GROWTH AND PRODUCTIVITY INDICATORS OF KARAKUL LAMBS - Ismoilov Komil Tuygunovich; Mukhitdinov Shavkat Mukhammedjanov (Western European Studies, 2024)
The article presents information on the relationship between live weight and serum enzymes at different ages, which are considered one of the characteristic indicators of the productivity of Korakul lambs, and indicators of the productivity of breeding animals.
Keywords: live weight; gene pool; genotype; phenotype